The Importance of Communication as Part of Organizational Culture on Work-Life Balance - Bernik, Mojca; Žnidaršič, Jasmina (Sodobni pristopi v kadrovskem managementu in izobraževanju, 2026)
Effective communication within an organizational culture is key to a successful work-life balance. Managers play a central role in this by fostering open communication and building trust to contribute to a positive working environment. Organizations that actively promote such a culture not only improve the well-being of their employees, but also enhance their competitiveness and sustainable development. Through a survey conducted in a healthcare institution in Slovenia, we aimed to find out whether there are differences in the perception of communication as part of organizational behaviour, whether there are differences in satisfaction with work-life balance according to gender, age and education, and how communication as part of organizational culture affects work-life balance. The paper offers an in-depth understanding of the role of organizational communication in work-life balance and offers new empirical insights into the impact of demographic factors on perceptions of the work environment.